Isolated psoas hydatidosis mimicking ovarian neoplasm - Baruah, Upasana; Barmon, Debabrata; Tak, Apoorva; Begum, Dimpy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
We report a unique case of hydatid cyst in iliopsoas muscle in a 65-year-old postmenopausal female. She presented with lump abdomen. On performing exploratory laparotomy, we discovered iliopsoas hydatidosis. This case reports the diagnostic dilemmas that a hydatid cyst can pose and the implications it has on management.